2006
DOI: 10.1007/s10517-006-0354-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum DNA in patients with rheumatoid arthritis is considerably enriched with fragments of ribosomal repeats containing immunostimulatory CpG-motifs

Abstract: We previously hypothesized that the sequence of transcribed region of human ribosomal repeats is selectively accumulated in circulating extracellular DNA due to its increased resistance to double-strand breaks caused by accumulation of single-chain breaks produced by nucleases. The contents of rDNA in blood serum DNA and in DNA from leukocytic nuclei both in healthy donors and in patients with rheumatoid arthritis were compared using dot hybridization method. By the content of non-methylated CpG-repeats, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…We showed that TRrDNA fragments have an in vitro stimulatory effect on lymphocytes. It may be suggested that selective accumulation of these fragments in extracellular DNA [1] may modulate function of the immune system. This work was supported by the Russian Foundation for Basic Research (grants No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that TRrDNA fragments have an in vitro stimulatory effect on lymphocytes. It may be suggested that selective accumulation of these fragments in extracellular DNA [1] may modulate function of the immune system. This work was supported by the Russian Foundation for Basic Research (grants No.…”
Section: Resultsmentioning
confidence: 99%
“…We described a previously unknown property of fragments from transcribed region of ribosomal repeat (TRrDNA): they are accumulated in extracellular peripheral blood DNA in healthy individuals and, especialy, in patients with rheumatoid arthritis (RA) [1]. The increase in the content of TRrDNA fragments in extracellular DNA is important for the immune system.…”
mentioning
confidence: 99%
“…Interestingly, it has been demonstrated that ribosomal DNA (rDNA) containing hypomethylated DNA released from host derived dead cells is present at increased levels in the RA serum (Veiko et al, 2006). This rDNA fragments are thought to stimulate TLR9 signalling.…”
Section: Toll-like Receptors (Tlr) In Ramentioning
confidence: 99%
“…Intraarticularly injected bacterial DNA containing CpG motifs induces transient arthritis and aggravates collagen-induced arthritis in mice [17,18]. The data suggest that DNA from dead cells circulating in the peripheral blood is capable of interacting with TLR9 receptors and enriched with sequences possessing potent immunostimulatory properties [19,29,30]. Recently, the increased expression of TLR9 in the peripheral blood B cells of RA patients versus healthy donors was reported, suggesting that TLR9 plays a role in the hyperreactivity of RA B lymphocytes [31].…”
Section: Introductionmentioning
confidence: 97%